Strategi Pencegahan Faltering Growth dengan Penguatan Pengetahuan Pangan Lokal dalam Pemberian MPASI - Harnawati, Riska Arsita; Andari, Istiqomah Dwi; Zulfiana, Evi; Arti, Tyas Dwi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Faltering growth is a child health problem that can lead to stunting if left untreated. The causes of faltering growth include inadequate nutritional intake during pregnancy and early life. The purpose of this PKM is to provide information to cadres and mothers of toddlers on the use of local foods in complementary feeding to prevent faltering growth. Method: PKM activities were carried out in Debong Kulon Village, Tegal Selatan Subdistrict, Tegal City, with cadres and women with children under five years old as participants. The method used in the activity was counseling. Results: The result of this activity is an increase in knowledge; it is hoped that it can be a benchmark that mothers already understand about proper complementary feeding, and can improve the routine of complementary feeding, so as to reduce faltering growth and even the incidence of stunting in order to improve the quality of children's health. Conclusion: Health education is crucial to improving public health. The material presented in the activity covers complementary foods, faltering growth, nutrition, and local foods.